A case report of missed abortion in cervical pregnancy - T Naderi (JRI, 2003)
Naturally, blastocyte implants in the uterine cavity. Implantation of blastocyst in any other place is considered an ectopic pregnancy, which is in more than 95% a tubal pregnancy. Cervical ectopic pregnancy is a rare type of ectopic pregnancy in wich blastocyte is implanted in the cervical canal. Therefore due to serious risks of cervical pregnancy, all obstetricians facing first-trimester vaginal bleedings should consider it as a differential diagnosis. In this article a case report of missed cervical pregnancy in a 32-year old woman is presented. The patient complained of temporary vaginal bleeding during the last 25 weeks. Sonography had been performed twice; the first one in the 12th week of gestation showing no fetal echo and the second in 22nd week of gestation showing a 27×12 mm mass and fluid in the endometrium. With the diagnosis of missed abortion suction curettage was performed at 25th week of gestation and it was lead to laparatomy due to active hemorrhage and clinical picture of deterioration of vital signs. During laparatomy, a dilated cervix completely invaded by throphoblasts was observed. Hysterectomy was performed with ovarian preservation as a final management. Pathologic findings showed complete implantation of placenta in the end cervix.
Keywords: Ectopic pregnancy, Cervical pregnancy, Missed abortion, Hystroscopy